Single-shot ultrafast imaging attaining 70 trillion frames per second - Peng Wang (Nature Portfolio, 2020)
Ultrafast imaging has been limited by the speed of electronic sensors. Here, the authors demonstrate single-shot compressed ultrafast spectral photography, which combines spectral encoding, pulse splitting, temporal shearing, and compressed sensing in order to achieve real-time imaging at 70 trillion frames per second.